Transformasi Ekonomi Kerakyatan Berbasis Pancasila dalam Menghadapi Disrupsi Ekonomi Digital - Ahmad Hafidz Kurniawan; Dewi Rahmawati Sholihah; Muhammad Badruzzaman Anwar (PT. Panca Publishing Indonesia, 2026)
The rapid acceleration of the digital economy creates structural disruptions that fundamentally challenge the sustainability and relevance of grassroots economic institutions based on Pancasila in Indonesia. The aim: This research seeks to explore transformation strategies for cooperatives and MSMEs rooted in Pancasila values to navigate digital economic disruptions and to develop a grounded, practical transformation model. Methodology: A qualitative approach with constructivist grounded theory involving 118 informants from cooperatives, MSMEs, and community economic organizations across five districts in Lampung through in-depth interviews, participatory observation, and document analysis. Results: Three transformation pathways were identified: organic-adaptive, disruptive-accelerative, and hybrid-synergistic, with the third pathway demonstrating the most sustainable outcomes through the integration of digital technology with the principles of gotong royong. Conclusion: The sustainable transformation of grassroots economics requires a value-first approach that grounds digital adoption in the ethics of cooperation and community-based Pancasila principles.